Search for single production of a vector-like T quark decaying to a Z boson and a top quark in proton–proton collisions at s=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (Elsevier, 2018)
A search for single production of vector-like quarks, T and B, decaying into a Z boson and a top or a bottom quark, respectively, is presented. The search is performed using data collected by the CMS experiment at the LHC in proton-proton collisions at √ s = 13 TeV, corresponding to an integrated luminosity of 2.3 fb−1 . An exotic T quark production mode through the decay of a heavy Z0 resonance is also considered. The search is performed in events with a Z boson decaying leptonically, accompanied by a bottom or a top quark decaying hadronically. No excess of events is observed over the standard model background expectation. Products of production cross section and branching fraction for T and B quarks from 1.26 and 0.13 pb are excluded at 95% confidence level for the range of resonance mass considered, which is between 0.7 and 1.7 TeV. Limits on the product of the Z0 boson production cross section and branching fraction, with the Z0 boson decaying to the Tt final state, are set between 0.31 and 0.13 pb, for Z0 boson masses in the range from 1.5 to 2.5 TeV. This is the first search at 13 TeV for single production of vector-like quarks in events with a Z boson decaying leptonically accompanied by boosted jets.